DISPARITAS GENDER DALAM PEMBANGUNAN PARIWISATA RAMAH LINGKUNGAN (Gender Disparities in Ecologically Friendly-Tourism Development) - Nurhaeni, Ismi Dwi Astuti; Sugiarti, Rara; Marwanti, Sri; Pratiwi, Ryza D (UIN Sunan Kudus, 2017)
This article explores gender disparities in ecologically friendly-tourism development, including the involvement, competence, internal and external barriers of women and men. The data were collected using survey on 400 respondents, consisting of women and men and focus group discussion with 18 informants. The data analysis uses analysis of gender disparities on planning, implementing, monitoring and evaluating the stage of ecologically friendly- tourism development. The finding shows that gender disparities happen in ecologically friendly- tourism development, in which women are still marginalized in terms of their involvement, competency, internal and external barriers. The highest gender disparities on the involvement of women and men in ecologically friendly-tourism development occurred in the implementation. Women’s competence is lower than that of men, and women‘s barrier are higher than that of men. Accordingly, gender mainstreaming in developing environmentally-friendly tourism should be empowered through gender based-financial allocation, especially for eliminating gender stereotip and improving human resources capacities in developing environmentally-friendly tourism.